Feeling economy - Loureiro, S. M. C.; Bilro, R. G. (Encyclopedia of tourism management and marketing, 2022)
The feeling economy is “an economy in which the total employment and wages attributable to feeling tasks exceed the total employment and wages attributable to thinking or mechanical tasks” (Huang, Rust, and Maksimovic, 2019, p. 44). In 2020 we are still living in a thinking economy in which were managers of the travel and hospitality industry value more analytical than empathic capabilities for their operational employees. However, increasingly artificial intelligence (AI) algorithms and AI robots are assuming analytical tasks (thinking) and managers and employees are using more and more their interpersonal, communicational, and empathic (feeling) capabilities to perform tasks. Feeling economy is an era where emphatic capabilities become more relevant than ever before. Researchers expect that the transition from thinking to feeling economy occur in 2036.